MASYARAKAT MADANI DALAM ISLAM - samsinas, Samsinas (Hunafa: Jurnal Studia Islamika, 2006)
In modern era, the idea of Madani Society is one of  alternatives in building society wished by the majority of Indonesian people. They associate the idea of Madani Society with that of Madinah Society established by the Prophet Muhammad during his life in Madinah. Although Madinah society was simple, it was regarded highly modern in that era. The idea of  Madani Society lies on the principle of  khaira ummah (the best adherents) in Islam. Therefore, Islam orders its ummah (adherents) to lead to Madinah Society. Kata Kunci: Masyarakat madani, civil society, masyarakat Madinah,    khaira ummah